Betacyanins, major components in Opuntia red-purple fruits, protect against acetaminophen-induced acute liver failure. (November 2020) - González-Ponce, Herson Antonio; Martínez-Saldaña, Ma. Consolación; Tepper, Pieter G.; Quax, Wim J.; Buist-Homan, Manon; Faber, Klaas Nico; Moshage, Han
Graphical abstract: Highlights: The major biocomponents in Opuntia red-purple fruits are betacyanins. The betacyanins-rich juices protect therapeutically against acute liver damage. The Opuntia juices reduce the gene expression of the cell stress sensor Gadd45b . The Opuntia juices modulate the expression of key antioxidant enzymes to protect the liver. Abstract: Acetaminophen (APAP) misuse or overdose is the most important cause of drug-induced acute liver failure. Overdoses of acetaminophen induce oxidative stress and liver injury by the electrophilic metabolite N -acetyl- p -benzoquinone imine (NAPQI). Plant-based medicine has been used for centuries against diseases or intoxications due to their biological activities. The aim of this study was to evaluate the therapeutic value of Opuntia robusta and Opuntia streptacantha fruit extracts against acetaminophen-induced liver damage and to identify the major biocomponents on them. Opuntia fruit extracts were obtained by peeling and squeezing each specie, followed by lyophilization. HPLC was used to characterize the extracts. The effect of the extracts against acetaminophen-induced acute liver injury was evaluated both in vivo and in vitro using biochemical, molecular and histological determinations. The results showed that betacyanins are the main components in the analyzed Opuntia fruit extracts, with betanin as the highest concentration. Therapeutic treatments with Opuntia extracts reduced biochemical, molecular and histological markers of liver ( in vivo ) and hepatocyte ( in vitro ) injury. Opuntia extracts reduced the APAP-increased expression of the stress-related gene Gadd45b . Furthermore, Opuntia extracts exerted diverse effects on the antioxidant related genes Sod2, Gclc and Hmox1, independent of their ROS-scavenging ability. Therefore, betacyanins as betanin from Opuntia robusta and Opuntia streptacantha fruits are promising nutraceutical compounds against oxidative liver damage.